FROM MOTIVATION TO MASTERY: A SYSTEMATIC LITERATURE SYNTHESIS OF GAMIFIED AND GAME-BASED APPROACHES IN ONLINE LEARNING ENVIRONMENTS - Eshankulov Shuxrat (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This paper synthesizes empirical and theoretical research comparing gamification and game-based learning (GBL) in online learning environments across higher education and professional contexts. Drawing upon Self-Determination Theory, Flow Theory, and Cognitive Load Theory, the study reviews empirical findings from 2012–2025 to evaluate how these approaches influence motivation, engagement, learning outcomes, and retention. Evidence suggests that both strategies can enhance engagement and learning, but they differ in scope and sustainability. Gamification improves short-term participation and measurable task performance, while GBL supports intrinsic motivation, deep learning, and long-term retention through meaningful interaction and narrative immersion. Design quality—particularly autonomy, feedback, narrative fidelity, and inclusivity—moderates effectiveness. This synthesis concludes that hybrid frameworks integrating gamified reinforcement with game-based learning contexts yield optimal outcomes in online education.